Estimating future smoking in Danish youth – effects of three prevention strategies. Issue 8 (December 2021) - Johannesen, Caroline Klint; Andersen, Susan; Bast, Lotus Sofie
Aims: Preventing smoking and aiding cessation among youth and young adults carries the possibility of reducing future smoking prevalence significantly. This paper estimates the impact on future smoking prevalence of 25 year olds by increasing tobacco prices, securing indoor smoke-free homes and implementing school-based multi-tiered interventions.Methods: Utilizing a multi-state Markov model, a status quo projection of the smoking prevalence from years 2017 to 2030 were compared with projections of the smoking prevalence in 2030 considering the impact of the three prevention strategies.Results: In a status quo projection, 27.0% of Danish 25-year-old females are expected to be smokers in 2030, while 13.2% would be smokers in 2030 were all three prevention strategies in effect from 2019. By itself, increasing tobacco prices by 50% reduced the prevalence of smokers among 25-year-old females to 14.8% in 2030, a relative reduction of 47.5%. For 25-year-old males in 2030 the reductions were similar, with a prevalence of 16.6% when all three prevention strategies were in effect, a relative reduction of 51.5%.Conclusions: Implementing increasing tobacco prices, indoor smoke-free homes and school-based multi-tiered interventions in Denmark is likely to significantly decrease youth smoking prevalence in the future. However, these three strategies will not produce a smoke-free generation without other initiatives.